Functionally Graded AISI 316L and AISI H13 Manufactured by L-DED for Die and Mould Applications - Marta Ostolaza; Jon Iñaki Arrizubieta; Aitzol Lamikiz; Magdalena Cortina (Applied Sciences, 2021)
Tooling in the die and mould industry is subjected to high-wear and high-temperature environments, which often leads to the premature failure of this high-added-value tooling. When severe damage occurs, an alternative to replacing the whole component consists of the repair by laser-directed energy deposition (L-DED). For that end, intermediate layers are commonly employed as buffer material, where introducing a functionally graded material (FGM) might be beneficial to avoid material incompatibilities and improve the overall performance of the tooling. In the present work, an FGM composed of gradient AISI 316L to AISI H13 has been manufactured, and its microstructure and hardness analysed. Firstly, cracking owing to the formation of brittle intermediate phases has been detected. Secondly, an increase of the hardness and a decrease of the corrosion resistance has been observed when transitioning from AISI 316L to AISI H13. Thirdly, despite the FGM composition evolving linearly, nonlinear material properties such as hardness and corrosion have been observed, which are conditioned by the microstructure formed during the L‑DED process and the nonlinear influence of the composition of steel on such properties. Consequently, nonlinear compositional gradients are recommended if linear mechanical properties are to be obtained in the case of steel FGMs.